1997
DOI: 10.1038/ki.1997.188
|View full text |Cite
|
Sign up to set email alerts
|

Latent transforming growth factor-β: Structural features and mechanisms of activation

Abstract: Transforming growth factor-beta are cytokines with a wide range of biological effects. They play a pathologic role in inflammatory and fibrosing diseases such as nephrosclerosis. TGF-beta s are secreted in a latent form due to noncovalent association with latency associated peptide (LAP), which is a homodimer formed from the propeptide region of TGF-beta. LAP is disulfide linked to another protein, latent TGF-beta binding protein (LTBP). LTBP has features in common with extracellular matrix proteins, and targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
362
2
15

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(380 citation statements)
references
References 69 publications
1
362
2
15
Order By: Relevance
“…Thrombospondin-1 is an adhesive glycoprotein component of the extracellular matrix (Sid et al, 2004). It binds and activates latent TGFb (Negoescu et al, 1995;Munger et al, 1997). Quantitative real-time RT-PCR analysis confirmed that the expression of both amphiregulin and thrombospondin-1 parallels the expansion of the ductal tree at puberty in a similar way to CITED1 (compare Figure 5B (a), (c) to Figure 1b).…”
Section: Cited1 In the Pubertal Mammary Gland J Howlin Et Almentioning
confidence: 60%
“…Thrombospondin-1 is an adhesive glycoprotein component of the extracellular matrix (Sid et al, 2004). It binds and activates latent TGFb (Negoescu et al, 1995;Munger et al, 1997). Quantitative real-time RT-PCR analysis confirmed that the expression of both amphiregulin and thrombospondin-1 parallels the expansion of the ductal tree at puberty in a similar way to CITED1 (compare Figure 5B (a), (c) to Figure 1b).…”
Section: Cited1 In the Pubertal Mammary Gland J Howlin Et Almentioning
confidence: 60%
“…20 Activation can be achieved by multiple tissue-and disease-specific mechanisms, including modification of the latent complex by reactive oxygen species, proteolysis, integrin binding, cellular contractility, and shear forces, or through binding to thrombospondin 1 (TSP1). [21][22][23][24] We identified the role of TSP1 as a major physiologic activator of latent TGF-␤.…”
mentioning
confidence: 99%
“…Latent-TGFβ1 must undergo cleavage from this complex in order to become activated. LTBP targets latent TGFβ1 to the extracellular matrix, where it interacts with the insulin-like growth factor II receptor (IGFIIR), itself a putative tumour suppressor gene (Munger et al, 1997). It is thought that IGFIIR orientates latent-TGFβ1 for proteolytic cleavage.…”
mentioning
confidence: 99%